PENGARUH KETIDAKAMANAN KERJA, KEPUASAN KERJA, DAN KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION PADA PT. RIAU CRUMB RUBBER FACTORY (RICRY) PEKANBARU - Auliya Annisa; Taufiqurrahman '; Kuniawaty Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine how the effects of job insecurity, job satisfaction and organizational commitment on turnover intention at PT. Riau Crumb Rubber Factory (RICRY) Pekanbaru. As for the population in this study were all employees of PT. Riau Crumb Rubber Factory (RICRY) Pekanbaru numbering 84 people and the entire population to be sampled in this study, so this research is census method .. Analysis of the data used is descriptive analysis with quantitative analysis tools that multiple linear regression with SPSS version 18.00. From the testing that has been done by the researchers showed that job insecurity, job satisfaction and organizational commitment simultaneously and partially significant effect on Turnover Intention at PT. Riau Crumb Rubber Factory (RICRY) Pekanbaru. In terms of turnover intention, the company should pay more attention and be able to anticipate early losses that will occur because the turnover of employees who want to quit the company and seek a job in another company so that the company does not lose competent human resources by considering the convenience of employees at work, job satisfaction of employees and organizational commitment and the company is able to achieve its goals. and the company should pay more attention to the perceived job insecurity of employees by providing certainty to the continued employment of employees, in the future.Keywords : Job Insecurity, Job Satisfaction, Organizational Commitment, and Turnover Intention